2017
DOI: 10.1021/acschemneuro.6b00395
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Assists Dopamine Release by Preventing Aggregation on the Inner Leaflet of Presynaptic Vesicles

Abstract: In this study, the dopamine-lipid bilayer interactions were probed with three physiologically relevant ion compositions using atomistic molecular dynamics simulations and free energy calculations. The in silico results indicate that calcium is able to decrease significantly the binding of dopamine to a neutral (zwitterionic) phosphatidylcholine lipid bilayer model mimicking the inner leaflet of a presynaptic vesicle. We argue that the observed calcium-induced effect is likely in crucial role in the neurotransm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 54 publications
(131 reference statements)
0
35
0
Order By: Relevance
“…3). This membrane preference of dopamine is predicted to be prevented almost entirely by the neutral MLC, and high calcium levels present inside the presynaptic vesicles based on the simulations and free energy calculations [58]. Nevertheless, the mechanisms for detachment of lipophilic NTs and drugs from various membranes in the synapse remain mostly unknown and, thus, require more scrutiny in the future.…”
Section: Presynaptic Vesicle: Three Fail-safes For Assuring Efficientmentioning
confidence: 98%
See 3 more Smart Citations
“…3). This membrane preference of dopamine is predicted to be prevented almost entirely by the neutral MLC, and high calcium levels present inside the presynaptic vesicles based on the simulations and free energy calculations [58]. Nevertheless, the mechanisms for detachment of lipophilic NTs and drugs from various membranes in the synapse remain mostly unknown and, thus, require more scrutiny in the future.…”
Section: Presynaptic Vesicle: Three Fail-safes For Assuring Efficientmentioning
confidence: 98%
“…Endocannabinoids such as anandamide, which are derived directly from fatty acids and act as retrograde transmitters [50], deep membrane penetration, and lipid-like dynamics, are to be expected, but the level of membrane permeation or adherence is less evident for the conventional NTs. In fact, several computational and experimental studies have provided solid evidence on the effects of specific NT-lipid interactions and, moreover, highlighted the potential importance of membrane lipid composition (MLC) imbalances for neurological diseases [42,48,[51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67].…”
Section: Evidence Of Direct Neurotransmitter-lipid Interactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The serotonin derived hormone melatonin associates with planar bilayers in a similar orientation, however this has only been measured qualitatively but not quantitatively (16,17). Another study indicated that the electrostatic interaction of dopamine with the inner leaflet of presynaptic vesicles must be screened to prevent NT aggregation and thus facilitate synaptic release (18).…”
Section: Introductionmentioning
confidence: 99%